Peningkatan Efisiensi Pengelolaan Sampah Melalui Sistem Informasi Berbasis Web: Studi Kasus Bank Sampah Sekar - Lontoh, Christian Alfa Romeo; Juliana, Cinta Putri; Yanti, Nur Riska Ayu Dwi; Putri, Nadia Amalia; Alvinania, Qeisa Dwiokta; Fattah , Farizi; Susilo, Marshanda Aura Zefanya; Hayati, Farida Nur; Hidayah, Farida Nur (Abdimas Universal, 2026)
The purpose of this community service is to improve the efficiency and transparency of waste management through the development of a web-based information system called SekarCycle at the Sekar Waste Bank in RT 18 Balikpapan. The background of this activity is the process of recording waste transactions that have been done manually, which tends to be inefficient, prone to errors, and difficult to track. Starting with field observations and determining partner needs, the activity continued with the creation of a digital system, user instructions, and the development of social media accounts as a means of education. The results of the activity showed the ability of the SekarCycle system to accelerate recording, improve data accuracy, and make transaction reports easier. Educational activities and ecoenzyme workshops also encouraged residents to use household waste management methods. This program shows that sustainable waste management at the community level can be achieved through the integration of appropriate technology and participatory methods.